Public Participation in Public Policy Implementation: Legal Analysis and Challenges in Indonesia - Diya Ul Akmal; Annisaul Maslamah; Dwi Sri Handayani; Taupik Hidayat (Indonesian Journal of Law and Syariah, 2026)
This study aims to determine the implementation of public policy in the theoretical realm. In addition, this study also aims to identify the obstacles to the implementation of public policy in applying community participation. This study is a qualitative study whose data was obtained through literature study. The approaches used include theoretical and conceptual approaches. The results show that community participation has a very significant influence on policy implementation. The success of public policy is determined by the community's willingness to participate in the policy. In addition, the government needs to play a role in increasing community participation in the implementation of public policy by providing access to information, increasing community capacity, and strengthening participatory mechanisms. Therefore, it is necessary to improve the methods used to encourage public participation in the process of formulating, implementing, and evaluating public policy.